The moral conflict of law and neuroscience - Alces, Peter A. (Chicago : The University of Chicago Press, 2018)
Law relies on a conception of human agency, the idea that humans are capable of making their own choices and are morally responsible for the consequences. But what if that is not the case? Over the past half century, the story of the law has been one of increased acuity concerning the human condition, especially the workings of the brain. The law already considers select cognitive realities in evaluating questions of agency and responsibility, such as age, sanity, and emotional distress. As new neuroscientific research comprehensively calls into question the very idea of free will, how should the law respond to this revised understanding? Peter A. Alces considers where and how the law currently fails to appreciate the neuroscientific revelation that humans may in key ways lack normative free will - and therefore moral responsibility.
Previously issued in print: 2018.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on September 3, 2018).
Keywords: Law and ethics; Free will and determinism; Neurosciences; Law; Jurisprudence & general issues; Law as it applies to other professions & disciplines; Criminal law: procedure & offences; Mental health law